Pengaruh Konten Marketing Parfum Crusita pada Live Streaming ‘Marapthon’ dalam Channel Youtube @ybrap Terhadap Awareness dan Minat Beli Audiens @ybrap - Fitri Yuwanita Wulandari; Sekar Awwaliyah Hussen; Trimanah Trimanah (Indo Publishing, 2026)
This research is motivated by the increasing use of live streaming as a digital marketing medium. Crusita utilizes the live streaming event “Marapthon” on the YouTube channel @ybrap as a content marketing strategy to increase audience awareness and purchase intention. This study aims to analyze the effect of content marketing in the “Marapthon” live streaming on audience awareness and purchase intention of @ybrap viewers. The study applies the Hierarchy of Effects theory, a quantitative approach with a positivist paradigm, and employs purposive sampling involving 100 respondents who watched the “Marapthon” live streaming on March 17, 2025. Data were analyzed using simple linear regression with IBM SPSS version 31. The results show that all questionnaire items are valid and reliable. The regression analysis indicates that content marketing has a significant effect on awareness by 24.3%, while the remaining 75.7% is influenced by other factors outside the study. In addition, content marketing also has a significant effect on purchase intention by 52.4%, while the remaining 47.6% is influenced by other factors. The t-test results show that content marketing has a positive and significant effect on both awareness and purchase intention of the audience. This study concludes that content marketing through live streaming is able to increase awareness and purchase intention in accordance with the stages of the Hierarchy of Effects theory. The limitation of this study lies in the sample, which only includes viewers from a single live streaming session, and the use of only one independent variable. Therefore, future research is suggested to expand the sample and include additional variables to obtain more comprehensive results.